2003
DOI: 10.1108/09615530310464517
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer to pulsating turbulent flow in an abrupt pipe expansion

Abstract: A numerical investigation aimed at understanding the flow and heat transfer characteristics of pulsating turbulent flow in an abrupt pipe expansion was carried out. The flow patterns are classified by four parameters; the Reynolds number, the Prandtl number, the abrupt expansion ratio and the pulsation frequency. The influence of these parameters on the flow was studied in the range 104<Re<5×104, 0.7<Pr<7.0, 0.2<d/D<0.6 and 5<f<35. It was found that the influence of pulsation on the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It shows that the Wammersley number has been reported [22,23]. Saeed et al [24] states that for liquids with a Prandtl number less than 1 in pulsating turbulence, a sudden expansion of the pipe was observed to increase the secular deviation of the heat transfer coefficient by around 10. Various turbulent models of pulsatile flow have been investigated to know the phenomenon of the influence of pulsation on the coefficient of heat transfer & to solve these complications with conflicting results.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It shows that the Wammersley number has been reported [22,23]. Saeed et al [24] states that for liquids with a Prandtl number less than 1 in pulsating turbulence, a sudden expansion of the pipe was observed to increase the secular deviation of the heat transfer coefficient by around 10. Various turbulent models of pulsatile flow have been investigated to know the phenomenon of the influence of pulsation on the coefficient of heat transfer & to solve these complications with conflicting results.…”
Section: Introductionmentioning
confidence: 88%
“…The effect of various input parameters on the Nusselt numbers are studied in last decade documented by some of the researchers [17][18][19][20][21]. This researcher showed the relationship between the Nusselt number and the amplitude and frequency of a numerical study of turbulent pulsatile flow conducted by several researchers [22][23][24], which is optimal for increasing heat transfer coefficient. It shows that the Wammersley number has been reported [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Said et al [7] have investigated flow and heat transfer characteristics of pulsating flow downstream of an abrupt expansion for different frequencies (5 to 35 Hz), Reynolds numbers (5 and 10·10 5 ), expansion ratios (0.2 and 0.6), and Prandtl numbers (0.7 and 7.0). They reported that the influence of pulsation on the mean time-averaged Nusselt number is insignificant for fluids having a Prandtl number less than unity, while the increase is around 30% for fluids having a Prandtl number greater than unity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Zemanick and Dougall [23] obtained different results for air flow at Re above 30000, especially at the peak of the Nusselt number. Said et al [24] carried out a numerical study of the heat transfer to fluid flow in an abrupt expansion with Re at 4•10 4 to 5•10 4 , an expansion ratio from 0.2 to 0.6 and a Prandtl number from 0.7 to 7. They observed that these boundary conditions have a significant effect on the mean time average Nusselt number with Prandtl number greater than unity.…”
Section: Introductionmentioning
confidence: 99%